المسنون ورعايتهم في ضوء القرآن الكريم : دراسة موضوعية - محمد سراج الإسلام بن محمد سلطان أحمد (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2013)
The research focuses on the care of the elderly in light of the Qur'an; religious care, health care, moral care, psychological care, as well as social welfare. It examines the Qur'anic verses that highlight the care of the elderly, the changes that occur to them, their needs, who is responsible for their care, the methods is used taking care of them, and the aspects of their care. This research relies on inductive methodology to collect Qur'anic verses as well as the Sunnah that talk about the elderly and the analytical method to analyze Qur'anic verses and Hadith related to this subject. Eventually, the research found that the Qur'an does not used the word elderly “Musin”, but there are synonyms which show explicit indication of the elderly as well as implicit indication. The research also found that Islam cares not only for the Muslim elderly but those from other faith also. Furthermore, the research claims that the basis of honoring human beings is demonstrated through care for this group in society. To care for the elderly, we must reform those responsible for them. All aspects of care for the elderly are interconnected; it would not be complete without each other.